Control of the intermetallic compound of the laser welding-brazing steel-Al joint and its effect on the joint property - Bolong Li; Jiayi Zhou; Hua Pan; Yu Sun; Tianhai Wu; Yulai Gao (Journal of Materials Research and Technology)
With the pursuit of improving fuel efficiency and vehicle performance in the automotive industry, automotive lightweight has become an important development direction. The joining of steel-Al dissimilar materials has great application prospects in the field of lightweight. In the present study, DP780 steel-5754 aluminum alloy joints were prepared by laser welding-brazing technique with ER4043 wire as the filler material. Various wire feed rates were chosen to elucidate their effect on the interface morphology and strength of the steel-Al joints. The strength and intermetallic compound thickness of steel-Al joints decreased as the wire feed rate increased. Interface microstructure of joints was determined as Fe–Al–Si intermetallic compounds. Under the condition of higher wire feed rate, intermetallic compound was too thin. However, intermetallic compound with a moderate thickness could be obtained by appropriately reducing wire feed rate. The ability of interfacial microstructure to hinder crack propagation was mainly influenced from two aspects: the thickness and toughness of intermetallic compound. At lower wire feed rates, Fe–Al–Si intermetallic compounds with appropriate thickness and good toughness were successfully produced and able to effectively resist the crack propagation along the interface. In this case, the specimens failed in the Al alloy base metal. Nevertheless, the interface became the weakened zone resulted from overly thin intermetallic compounds formed under the condition of higher wire feed rates. As a result, the specimens fractured in the interface zone. Thus, the thickness and nature of intermetallic compound became the crucial factors to determine the strength of steel-Al joints.